2003
DOI: 10.1111/1468-0009.00040
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic in the United States: Trends and Issues

Abstract: From its origins as an unconventional therapy in the late 19th century through decades of marginalization during the 20th century, chiropractic has acquired legitimacy and prominence (Meeker and Haldeman 2002). Signs of its success abound. They include a broadening of the laws and regulations affecting its licensure, scope of practice, and reimbursement; greater acceptance by both physicians and health plans; and a sustained demand for its services. Chiropractic's political base is strong, and it enjoys a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 94 publications
0
60
0
Order By: Relevance
“…7,16,26,27 Patients consistently express more satisfaction with chiropractic care than allopathic care and also return more often to doctors of chiropractic when their symptoms recur. 7 It was found that 95.8% of chiropractic patients indicated an overall satisfaction with chiropractic care and chiropractic services. 26 Chiropractic patients have reported receiving more self-care advice, as well as clearer explanations about their conditions and rationale for treatment, than do patients of MDs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,16,26,27 Patients consistently express more satisfaction with chiropractic care than allopathic care and also return more often to doctors of chiropractic when their symptoms recur. 7 It was found that 95.8% of chiropractic patients indicated an overall satisfaction with chiropractic care and chiropractic services. 26 Chiropractic patients have reported receiving more self-care advice, as well as clearer explanations about their conditions and rationale for treatment, than do patients of MDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 50% of back disorder cases lack a precipitating event, leading researchers to conclude that most LBP is a multifactorial syndrome. 6 Symptoms are usually attributed to one or more potential causes including poor muscle tone; muscle tension; muscle tears; injury to tendons, ligaments, nerves, or disks; and the resulting inflammation, 7 although in most cases there is no definite diagnosis made of the pain generator.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations